2020
DOI: 10.1021/acsami.0c13161
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation Mechanism in High-Entropy Oxides as Anode Materials for Li-Ion Batteries: An Operando XAS Study

Abstract: High-entropy oxides based on transition metals, such as Mg0.2Co0.2Ni0.2Cu0.2Zn0.2O (TM-HEO), have recently drawn special attention as potential anodes in lithium-ion batteries due to high specific capacity and cycling reversibility. However, the lithiation/delithiation mechanism of such systems is still controversial and not clearly addressed. Here, we report on an operando XAS investigation into TM-HEO-based anodes for lithium-ion cells during the first lithiation/delithiation cycle. This material showed a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 41 publications
7
104
0
Order By: Relevance
“…Upon further cycling, the acoustic behavior (in terms of cumulated hits and hit rate) in the delithiation cycles was similar. Comparable observations have been made for Si anodes 34 , thus indirectly corroborating the alloying/dealloying reaction mechanism proposed by Ghigna et al 16 Acoustic activity was found in the voltage ranges of 1.0–2.5 V (2nd and 3rd cycles) and 1.3–2.5 V (4th and 5th cycles). The shift to higher voltages with increasing cycle number is also evident from the contour plot in Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Upon further cycling, the acoustic behavior (in terms of cumulated hits and hit rate) in the delithiation cycles was similar. Comparable observations have been made for Si anodes 34 , thus indirectly corroborating the alloying/dealloying reaction mechanism proposed by Ghigna et al 16 Acoustic activity was found in the voltage ranges of 1.0–2.5 V (2nd and 3rd cycles) and 1.3–2.5 V (4th and 5th cycles). The shift to higher voltages with increasing cycle number is also evident from the contour plot in Fig.…”
Section: Resultssupporting
confidence: 87%
“…However, the crystal structure was still detectable by ex situ SAED. Recent X-ray absorption spectroscopy (XAS) studies have shown that the initial lithiation/delithiation processes are incomplete and irreversible 16 , leading to the formation of a mixture of metals and metal oxides, and that alloying and dealloying reactions with Li are involved in the charge-storage mechanism in the subsequent cycles (typical of ZnO and MgO anodes). Overall, this somewhat limits the possibility of operando investigations beyond the first cycle and, in particular, hinders further understanding of the reaction and degradation mechanisms under realistic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[13] High-entropy oxide, i. e., Mg 0.2 Co 0.2 Ni 0.2 Cu 0.2 Zn 0.2 O (TM-HEO) has been synthesized by Ghigna et al and tested as a new type anode for LIBs. [16] The adjustment of electronic and local structure on the TM-HEO was investigated by operando XANES, which confirmed that the lithiation process of TM-HEO included two steps. Firstly, the reductive transformation of Cu 2 + , Co 2 + , and Ni 2 + occurred from 1.2 V to 0.5 V, which was consistent with the shoulder peaks (8982, 8335, and 7712 eV) of XANES for Cu, Ni, and Co, respectively.…”
Section: Conversionmentioning
confidence: 64%
“…[7] Based on the evolution of optics, electronics, thermodynamics and magnetism, various in-situ/operando techniques including X-ray diffraction (XRD), X-ray absorption spectroscopy (XAS), transmission electron microscopy (TEM), Raman spectra and magnetometry have been developed (Table 1). [8][9][10][11][12][13][14][15][16][17][18][19] Among these techniques, Raman spectra is a powerful tool to characterize the short-range order (local environment) structure of lattice and electronic properties, though it is hard to achieve quantitative analysis. In-situ Raman mainly reveals the interfacial and structural changes like the formation process of SEI layer, and the electronic properties of ionic graphite intercalation compounds (GICs).…”
Section: Introductionmentioning
confidence: 99%
“…Since the concept of HEO anode was first proposed by Sarkar et al in 2018, various HEO anode materials such as rock salt-type (RSHEO) [9], perovskite-type (PHEO) [10] and spinel-type (SHEO) [11] have been developed. Nevertheless, due to lack of accurate characterization, the lithium storage mechanism of the HEO anode has not been studied carefully [12].…”
Section: Introductionmentioning
confidence: 99%